Comprehensive mechanism of ferromagnetism enhancement in nitrogen-doped graphene. (6th October 2021) - Di, Maoyun; Fu, Lin; Zhou, Yuan; Pan, Hongzhe; Xu, Yongjie; Du, Youwei; Tang, Nujiang
Abstract: Realizing the strong ferromagnetism (FM) with both the Curie temperature above room temperature and high magnetization in graphene, is key for its real application in future spintronics. Nitrogen-doping has been confirmed to be one of the most promising ways for experimental realization of room temperature FM in graphene. However, the comprehensive mechanism, which needs to verify the enhancements of both the nitrogen complexes-induced magnetism and the FM coupling among them, remains to be completely explored, which impedes the experimental optimization of the FM in nitrogen-doped graphene (NG). Here, we theoretically perform a comprehensive analysis on the FM enhancement in NG. The enhancement of both the magnetic moments and FM coupling highly depends on the N concentration and relative geometric configuration of the N complexes. Especially, the magnetic moments and FM coupling are attributed to the σ – π magnetic interaction between the localized and itinerant moments, the band reconstruction originated from the proximity of N complexes, and the sublattice match/mismatch. The FM enhancement is high sensibility to the geometric configurations of the N complexes, and only the presence of graphitic-3N combined with trimerized pyridine can realize the sublattice-independent strong FM in the high N-concentration limit. Whereas the low N-concentration limit favors the substantial FM enhancement in all systems, but would unavoidably undergo both the low Curie temperature and low magnetization due to the relatively low N-concentration. We hope that the comprehensive mechanism of FM enhancement we offered can push the optimization of the FM in NG via tuning its N concentration and geometric configuration of the N complexes by the rational design of the specific experimental strategies.